Optimization of a fluorogenic assay to determine caspase 3/7 activity in meat extracts - Fuente-Garcia, Claudia (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2022)
Usefulness of general-purpose fluorogenic assay kits to determine caspase 3/7 activity of biological extracts is highly compromised in meat-based samples due to their scarce enzyme concentration. In the present work, a straightforward protocol is presented with two main purposes: 1) to enhance sensitivity of the fluorogenic approach addressing caspase 3/7 activity in tissues showing scarce enzyme concentration such as skeletal muscle, and 2) to reduce/economize the volume of employed reagents. The enzyme extraction procedure, peptide substrate, dithiothreitol concentration and detection settings were appropriately optimized for use in microtiter-plate fluorometers. As a result, low to high enzyme activity extracts (from 10,000 to 260,000 relative fluorescence units) can be measured under developed sampling and experimental conditions. The fact that enzyme reactions took place in 96-microtiter well plates reduces the consumption of chemical compounds when analysing a high number of samples, thus contributing to environment sustainability